PERBEDAAN KEBUGARAN FISIK DAN ASPEK AFEKTIF SEBAGAI EFEK DARI PELATIHAN KIDS ATHLETICS DAN PERMAINAN TRADISIONAL MEGALA-GALA - Seran, Yohanes; Adiputra, N.; Purnawati, Susy; Jawi, I Made; Muliarta, Made; Griadhi, Putu Adiartha (Sport and Fitness Journal, 2017)
Background: Lack of physical activity is often caused by a lack of motivation as well as children today are more interested in modern games or online games. Objective: The purpose of this study was to determine differences in physical fitness and affective aspects as the effect of training kids athletics and traditional games Megala-gala on male students of SDN 14 Pemecutan Denpasar. Method: This research uses experimental design, Pre-Post test Control Group Design on 24 students aged 10-12 years. Were selected randomly and were divided into 2 groups. The first group was given training kids athltics and Group II was given the traditional game Megala-gala. Training is given three times a week for 6 weeks. Physical fitness was measured using a test run of 600 meters, while affective measured after training using a questionnaire. Ananlisis use significance level 0, 05. Result: The results of this study indicate that there are significant differences in physical fitness and affective aspects after intervention between groups with p = 0.00, but it also found significant differences in each group with a value of p = 0.00. Group I found a mean baseline of 3.24 ± 0.07 minutes increased to 2.38 ± 0.15 minutes (enchancement 26%) and in Group II preliminary data increased by 3.24 ± 0.11 minutes to 2.98 ± 0.11 minutes (enchancement 8%). On the affective aspects significant differences in; cooperation and responsibility with a value of p <0.05. Conclusion: It was concluded that training kids athletics further improve the physical fitness than the traditional game-Megala-gala but kids athletics training no more effect on the affective aspect than traditional game Megala-gala.